Implementasi Manajemen Resiko Pembiyaan Pada BSI KCP Mojokerto Bangsal - Sakhirotul Muffrikha; Fitri Nur Latifa; Masruchin Masruchin (ITB AAS INDONESIA Surakarta, 2021)
This study discusses the implementation of risk management financing at BSI KCP Mojokerto Bangsal which aims to find out about the implementation of risk management financing at BSI KCP Mojokerto Bangsal. This research is descriptive qualitative. This study uses secondary data in the form of literature to examine written sources such as scientific journals, literature, articles and other sources that are relevant and related to the object under study and primary data in the form of observations, interviews and documentation in the form of texts and pictures taken by researchers. then reprocessed. The result of this research is that Indonesian banking is now enlivened by the presence of Islamic banks that offer financial services products at BSI. This banking product also has a variety of risks, therefore the researcher clarifies the risks in Islamic banks and the application of risk management agreements in Islamic banks. Keywords : Islamic Banking, Risk Management, Implementation of Risk Management Financing